Recovery of defects of the cellular progress of the lower jaw as a guarantee of successful orthopedic treatment - Stupnytskyi І.-О. Р.; Rozhko М. М.; Stupnytskyi Р. М. (Actual Dentistry, 2022)
The aim of the work was to study the peculiarities of the choice of the newest methods of reconstruction of bone and tissue defects of the cellular process of the jaw. With Smart Dentin Grinder, you can easily turn a removed tooth into a dentin autograph ready for transplantation in just a few short steps. That will provide a sparing fence, full biocompatibility, high ostogenerating potential of autoplastic material, which can serve as removed teeth, which become grafts.